Advances in Food Processing Technology - Jia, Jingdun; Liu, Donghong; Ma, Haile (Springer Nature Singapore : Imprint: Springer, 2019)
This book introduces readers to essential advances in the application of physical processing technology in food processing that have been made in recent years. It analyzes and describes the application of Power Ultrasound, Pulsed Electric Field, Supercritical-CO2, and Infrared Heating in the contexts of food sterilization, extraction, modification, drying and safety control. Covering all aspects of food physical processing, from basic principles to the latest technological developments, it offers a valuable application guide for food engineers and food researchers alike. .